Transformation Beyond COVID-19: Accessibility in Lived Experience Involvement in Research Post Pandemic. Experience, Reflections and Future Direction From the Closing the Gap Network and OWLS Study - Walker, Lauren; Crosland, Suzanne; Johnston, Gordon; Peckham, Emily J. (Frontiers in Psychiatry, 2022)
Research literature published during the Covid-19 pandemic highlights the loss of involvement opportunities for people with lived experience during the pandemic as well as the vital role lived experience advisors play at all times, including highlighting unseen aspects of the impacts of crises such as the Covid-19 pandemic. During the pandemic, researchers from the Closing the Gap Network (CtG) at the University of York worked to expand and diversify patient and public involvement (PPI) whist working on a study exploring the impact of the pandemic and associated restrictions on those with the most severe forms of mental ill health. CtG had a strong record of patient and public involvement pre-pandemic and researchers wanted to ensure that this continued during the pandemic. This paper describes the experience of lived experience involvement during the pandemic from multiple perspectives and makes recommendations for future involvement models, accessibility and recommendations for future research.